The application of surface response methodology to the pretreatment of WC substrates prior to diamond coating - Shirdar, Mostafa Rezazadeh (Springer, 2014)
High cobalt (Co) content greater than 10% in tungsten carbide is desirable because Co improves the toughness of the cutting tool. However, the additional Co poses a huge challenge in surface preparation given that the Co content must be reduced to less than 1% on the substrate surface prior to applying a diamond coating. The excessive presence of Co on the substrate surface during coating suppresses diamond nucleation and causes the deterioration of diamond film adhesion. Many attempts have been made to overcome this issue, including the use of chemical etching, mechanical blasting, and heat treatment, but the successful pretreatment of WC-12%Co is still very limited. In this paper, a single-step chemical pretreatment using a mixture of sulfuric acid and hydrogen peroxide solutions was carried out on WC-12%Co. Two independent variables, i.e., etching time and acid temperature, were varied in the experiments to reduce Co contents as well as to roughen the substrate surface. The experimental plan was based on a central composite design. Variance analysis was employed to verify the precision of the mathematical models and their relative parameters. The predicted models generated by the response surface methodology (RSM) were compared with the experimental results, and close agreement was observed. The models demonstrated the significance of both factors, namely, acid temperature and etching time, in reducing Co contents to less than 1% as well as a roughening of the substrate surface within the desirable range.